1995
DOI: 10.1111/0031-868x.00024
|View full text |Cite
|
Sign up to set email alerts
|

Deville and Photographic Surveying

Abstract: Photographic surveying by Deville was published in 1895. This article marks the centenary of the publication of one of the earliest English language books on photogrammetry. Deville and his surveyors were responsible for the mapping of large areas in western Canada by photographic means. The techniques were explained in his book, originally written for his own staff when he was Surveyor General of Canada.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…From then on, photogrammetry became one of the most successful and widespread fields of application for photography (Meydenbauer 1912;Ollivier 1929;Weiss 1913; see also Atkinson 1995;Ponstingl 2001;Ponstingl 2002). Since the late 1850s, mostly military engineers had thought about applying photography in geodesy and cartography.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From then on, photogrammetry became one of the most successful and widespread fields of application for photography (Meydenbauer 1912;Ollivier 1929;Weiss 1913; see also Atkinson 1995;Ponstingl 2001;Ponstingl 2002). Since the late 1850s, mostly military engineers had thought about applying photography in geodesy and cartography.…”
Section: Resultsmentioning
confidence: 99%
“…But only from the 1880s on, was the procedure advanced enough to be professionally employed. From then on, photogrammetry became one of the most successful and widespread fields of application for photography (Meydenbauer 1912; Ollivier 1929; Weiss 1913; see also Atkinson 1995; Ponstingl 2001; Ponstingl 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was François Arago, a member of the French legislature and a noted astronomer, who championed Daguerre and also perceived the potential of photography for topographic applications (Flemer, ). Atkinson () notes that von Gruber (, p. 148) reported that as early as 1851 (just a year after producing the Panthemont façades in Fig. (b)) Laussedat had used photography in place of the camera lucida.…”
Section: Laussedat's Use Of Photographymentioning
confidence: 99%
“…This journal primarily publishes research at the forefront of developments in photogrammetry. However, from time to time we publish both reviewed papers (for example, Atkinson (, ) or Petrie and Nolan ()) and Editorials (such as Granshaw, ) that look back at the development of our discipline over many decades. Many of our recent authors have used terminology (such as intrinsic parameters rather than interior orientation parameters ) more akin to usage in computer vision, a much younger discipline than photogrammetry.…”
mentioning
confidence: 99%